Polarity study of ionic liquids with the solvatochromic dye Nile Red: a QSPR approach using in silico VolSurf+ descriptors. Issue 23 (9th June 2016) - Paterno', Alessio; D'Anna, Francesca; Fortuna, Cosimo G.; Musumarra, Giuseppe
Abstract: The in silico VolSurf+ descriptors, accounting for both cationic and anionic structural features of ionic liquids (ILs) were used to develop a Partial Least Squares (PLS) model able to establish a Quantitative Structure Property Relationship (QSPR) correlation with their solvatochromic dye Nile Red polarity. The PLS model allowed prediction of ENR values for 116 ILs providing an in silico ILs polarity database. Graphical abstract: